The Emergence of Standard English - Fisher, John H. (Book collections on Project MUSE., 1996)
"In these nine essays Fisher chronicles his gradual realization that Standard English was not a popular evolution at all but was the direct result of political decisions made by the Lancastrian administrations of Henry IV and Henry V - decisions intended to validate their usurpation of the English throne from Richard II and to create a new sense of nationalism. To achieve this standardization and acceptance of the vernacular, these kings turned to their Chancery scribes, who were responsible for writing and copying legal and royal documents." "Henry IV and V also made special use of authors in their promotion of English as the national language, and Chaucer played a central role in this language planning. None of Chaucer's writings, nor those of any English author, had been copied and circulated before Henry IV's accession in 1399. Once the Lancastrians decided to elevate English to the level of a national language, and thus to replace the French and Latin that had previously been the standard language of government and letters, they looked for appropriate models to disseminate." "Chaucer, a relative of the king and a superb writer in the vernacular, began to be labeled as an ideal master of language, and it was Henry V who inspired the fifteenth-century tradition of citing Chaucer as the "maker" of English. Even more important to linking language development to the government establishment, however, is the fact that Chaucer himself composed in the English of the Chancery scribes."--Jacket.